EFFECT OF SAHA AND C-JUN N-TERMINAL KINASE INHIBITOR ON THE INDUCIBLE MRNA EXPRESSION OF INTERLEUKIN-17 - Boncho Grigorov; Magdalena Platikanova; Zlatka Dobreva; Antonia Grigorova; Spaska Stanilova (Peytchinski Publishing, 2023)
Interleukin-17 (IL-17A) is a critical cytokine for immune defence against extracellular bacterial and fungal infections. Excess production during chronic inflammation has been associated with many inflammatory and autoimmune disorders. On the other hand, the inducible expression of many cytokine genes is regulated by the receptor-activated intracellular signaling pathways, including the JNK pathway, and different epigenetic mechanisms, including histone deacetylation by HDACs. We investigated the comparative effect of the HDACs inhibitor Suberoylanilide Hydroxamic Acid (SAHA) and an inhibitor of the JNK signaling pathway in the regulation of the inducible IL-17 expression at the mRNA level in PBMCs from healthy donors. For the detection of IL-17 mRNA transcripts was used qRT-PCR. We detected significantly increased levels of IL-17mRNA under the stimulation of the PBMC cultures with lipopolysaccharide (LPS) or C3 binding glycoprotein (C3bgp) in the presence of an inhibitor of the JNK transduction pathway. The inhibition of the JNK signaling pathway leads to the upregulation of the expression of IL-17mRNA. SAHA did not demonstrate a significant effect on the IL-17mRNA transcription compared to the inhibitor of the JNK pathway. In conclusion, we suppose that the synthesis of IL-17 mRNA is regulated by both the JNK transduction pathway and HDAC activity, but with different effects.